Numerical Investigation of Bundled RC Column under Impact Load - Abreha Abay; Temesgen Wondimu (Advances in Civil Engineering)
Dynamic impact load has an extensive application area in civil engineering, including highway, military, and marine structures. Many researchers have studied the performance of reinforced concrete (RC) columns under impact load. However, very limited work has been conducted on the effect of bundle reinforced concrete (BRC) columns subjected to lateral impact load. In this study, to examine the behavior of RC columns under impact load, numerical simulations of one with normal reinforcement distribution and three different bundles of reinforced concrete column specimens have been conducted using an explicit finite element (FE) analysis. In addition to the bundle reinforcement distribution, the parameters considered in the study are impact scenarios, impact velocity, pure axial load, and impact locations. From the numerical analysis, it has been found that bundling of longitudinal reinforcement does not only improve the impact capacity but also stabilizes the fluctuating response of impacted reinforced concrete columns. Both peak impact force and maximum lateral displacements of impacted BRC columns increase with increasing initial impact velocity. The numerical results also show that pure axial load slightly improved the impact capacity of the BRC columns. Finally, while the global failure of the RC column governs the response of repeatedly impacted BRC columns, failure characteristics of the single impacted columns are associated with local concrete damage at the impact zone.